Wage rigidities, barriers to entry and the welfare state: Their impact on labor markets in industrialized countries - Dean Spinanger (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1983)
The above quotes exemplify quite well the strange world in which we live: on the one hand governments over the last 30 years have generally attempted to enact measures to liberalize international trade (and as a matter of fact the movement of factors of production) so as to be able to profit - in the form of higher employment levels - from a more efficient allocation of resources. On the other hand, in many of the same countries governments (and/or unions) have effected (or supported) measures for domestic labor markets, the impact of which runs counter to the expected gains from a reduction in trade barriers. In other words, while a rapid expansion of international trade may have contributed significantly to creating employment, measures affecting the training, employment, remuneration and/or social security of the working-age population may well have caused jobs or job opportunities to disappear or job-seeking activities to be otherwise structured.
Keywords: 330